PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION DALAM MENINGKATKAN AKTIVITAS BELAJAR IPA SISWA DI KELAS VIII – 11 SMP NEGERI 4 MEDAN - JETTI SIMBOLON (JURNAL HANDAYANI PGSD FIP UNIMED, 2014)
The research is obtained for looking the science studying activites increasing which disembogue on the students’ learning outcomes while doing in group in class on science subjects by applicated the cooperative learning model type Student Team Achievement Division (STAD). The research subject was taken in class of VIII – 11 SMP Negeri 4 Medan by the amount of 32 students. The initially teaching – learning process was done the learning outcomes test (Pretest), by the average of data is 14,6 that is indicated the average of students seldom read the books before learning in school. Then, continued the teaching – learning process, the end of teaching – learning process II and IV is done the learning outcomes test for formative II and formative IV, which the result is indicated the average mark in formatif I  is 56,8 by the classical completeness is 62,5% and the average is 87,5 by the classical completeness is 87,5%. Looking of the data that is a increasing and the increasing is effected teacher acting during teaching – learning on cylce II. The student activites accord the observer observation on cylce I among others writing / reading (44&), doing the asssessment (20%), asking for friend (14%), asking for teacher (6%) and not relevant with teaching – learning process (16%). The student activity data accord the observation on cycle II among others writing / reading (16%), doing assessment (46%), asking for friend (21%), asking the teacher (12%) and not relevant with teaching – learning process (6%). The application of cooperative learning model type Student Team . Achievement Division (STAD) during the teaching – learning make students were happy, and comfortable.   Keywords: Cooperative learning model type Student Team Achievement Division (STAD), learning activities, learning outcomes